Reliability of nociceptive monitors vs. standard practice during general anesthesia: a prospective observational study - Daniel Widarsson Norbeck; Sophie Lindgren; Axel Wolf; Pether Jildenstål (BMC Anesthesiology, 2025)
Abstract Background Inadequate or excessive nociceptive control during general anesthesia can result in significant adverse outcomes. Using traditional clinical variables, such as heart rate, systolic blood pressure, and respiratory rate, to assess and manage nociceptive responses is often insufficient and could lead to overtreatment with both anesthetics and opioids. This study evaluated the feasibility and effectiveness of three nociception monitoring techniques Nociception Level Index (NOL), Skin Conductance Algesimeter (SCA) and heart rate monitoring in patients undergoing image-guided, minimally invasive abdominal interventions under general anesthesia. Method This prospective observational study collected data from 2022 to 2024. All patients were anesthetized according to the department’s routine, and predetermined events were recorded. Two commercially available nociception monitors, the PMD-200 from Medasense (NOL) and PainSensor from MedStorm (SCA), were used, and their data were collected along with various hemodynamic parameters. The three nociception monitoring techniques were compared during predetermined events. Result A total of 49 patients were included in this study. NOL and SCA demonstrated higher responsiveness than HR for all events except for skin incision. The comparison of the values above and below the threshold for each nociceptive stimulus showed significance for all measurements using the SCA and NOL. However, using HR as a surrogate for nociception with a threshold of a 10% increase from baseline, the difference was significant only at skin incision. There was no variation in the peak values attributable to differences in patients’ age. Weight was a significant predictor of the peak NOL values. Conclusion NOL and SCA demonstrated superior sensitivity and responsiveness to nociceptive stimuli compared to HR, effectively detecting significant changes in nociceptive thresholds across various stimuli, although responses during skin incision showed no such advantage. Trial registration Clinical trial - NCT05218551.